Pemasangan feeding plate dan ikatan ekstra oral pada bayi celah bibir dan langit-langit bilateral komplit disertai premaksila protrusif The utilization of feeding plate with extra oral strapping in infant with complete bilateral cleft lip and palate with protrusive premaxilla - Lisda Damayanti (Journal of Dentomaxillofacial Science, 2012)
Cleft lip and palate abnormalities in infant are the most common birth defect. This abnormality caused by failure of thefusing at the middle side of the facial frame on the week 4 to 10 of pregnancy. This abnormalities may occur togetheror separately. The coordination of the lip, tongue, palate and jaws become inadequate so there is changes in the abilityto suck, to swallow, weak muscle function and oral structure function so that the infant maybe unable to suck properly.Feeding plate use to overcome disproblem, so that the infant can have good nutrition. In infant with complete bilateralcleft lip and palate with protrusive premaxilla the utilization of this feeding device with the strapping extra oral rubberelastic orthodontic and hypapix is sure. In this paper will be discuss the utilization of device with the addition elasticorthodontic rubber in patient with complete bilateral cleft lip and palate. This feeding intervention is quiet effective, thesucking reflects of the infant become stronger and the premaxilla profile becomes more retruded that makes thesurgeon get an optimal surgical result easier.